1999
DOI: 10.1002/(sici)1520-6629(199909)27:5<589::aid-jcop6>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Promoting academic success and preventing disruptive behavior disorders through community partnership

Abstract: Research suggests that children's educational achievement can be improved by addressing issues of aggression and disruptive behavior, because academic difficulties and problem behaviors create a cycle in which each problem exacerbates the other. The relationship between academic development and behavior problems begins early, suggesting that programs to address these issues should start with young children. Furthermore, efforts to improve achievement are most likely to succeed when they focus both on children'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 28 publications
(29 reference statements)
2
44
0
Order By: Relevance
“…Thus, children who have difficulties in focusing, complying with rules, collaborating with other kids, controlling negative emotions, anger and stress are less adapted to school (Arnold et al, 1999;McClelland, Morrison, & Holmes, 2000). The results demonstrated that academic achievements in the first few years of school seem to be built on a solid basis of children's socio-emotional skills (Ladd, Kochenderfer, & Coleman, 1997, O'Neil et al, 1997as cited in Raver, 2003.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, children who have difficulties in focusing, complying with rules, collaborating with other kids, controlling negative emotions, anger and stress are less adapted to school (Arnold et al, 1999;McClelland, Morrison, & Holmes, 2000). The results demonstrated that academic achievements in the first few years of school seem to be built on a solid basis of children's socio-emotional skills (Ladd, Kochenderfer, & Coleman, 1997, O'Neil et al, 1997as cited in Raver, 2003.…”
Section: Problem Statementmentioning
confidence: 99%
“…Psychologists found that children who are antisocial in their behaviour are less accepted by peers and teachers (Kupersmidt, & Coie, 1990;Shores, & Wehby, 1999, as cited in Raver, 2003, participate less frequently and often deficiently in the classroom activities compared to their counterparts with a pro-social conduct. However, we should mention the fact that the relationship between the early academic skills of children and their socio-emotional adaptation can be bidirectional, meaning that those children who struggle with early learning difficulties could grow increasingly frustrated and aggressive (Arnold et al, 1999).…”
Section: Problem Statementmentioning
confidence: 99%
“…Such negative teacher-child exchanges have been associated with children's aggressive and oppositional behaviour, social withdrawal, diminished classroom participation and cooperation, and decreased liking of school (Arnold et al, 1999;Arnold, Griffith, Ortiz, & Stowe, 1998;Birch & Ladd, 1997;Campbell & Ewing, 1990;Carr, Taylor, & Robinson, 1991;Howes, Hamilton, & Matheson, 1994;Ladd & Burgess, 2001). …”
Section: Reactive Classroom Managementmentioning
confidence: 99%
“…Children with behavioural difficulties have been found to experience more negative interactions with their teachers and receive less positive teacher feedback and support (Arnold et al, 1998;Arnold et al, 1999;Campbell & Ewing, 1990;Carr et al, 1991). Some of the most frequently employed strategies for classroom management involve teacher statements of disapproval, verbal reprimands, and child exclusion (Bacon, 1990;Turner & Watson, 1999).…”
Section: Reactive Classroom Managementmentioning
confidence: 99%
“…Further, children with conduct problems are also more likely to be disliked by teachers, receive less academic or social 8 support, and obtain less positive feedback from teachers (e.g., Arnold et al, 1999). As a result, children with conduct problems find school less enjoyable, have lower school attendance, and are at an increased risk for underachievement, academic failure, and future adjustment problems (Birch & Ladd, 1997;Webster-Stratton et al, 2008).…”
Section: Early Intervention For Social and Behavioral Problemsmentioning
confidence: 99%